Perspective Insights to Bio-Nanomaterials for the Treatment of Neurological Disorders - Khan, Johra; Rudrapal, Mithun; Bhat, Eijaz Ahmed; Ali, Ahmad; Alaidarous, Mohammad; Alshehri, Bader; Banwas, Saeed; Ismail, Randa; Egbuna, Chukwuebuka (Frontiers in Bioengineering and Biotechnology, 2021)
The significance of biomaterials is well appreciated in nanotechnology, and its use has resulted in major advances in biomedical sciences. Although, currently, very little data is available on the clinical trial studies for treatment of neurological conditions, numerous promising advancements have been reported in drug delivery and regenerative therapies which can be applied in clinical practice. Among the commonly reported biomaterials in literature, the self-assembling peptides and hydrogels have been recognized as the most potential candidate for treatment of common neurological conditions such as Alzheimer’s, Parkinson’s, spinal cord injury, stroke and tumors. The hydrogels, specifically, offer advantages like flexibility and porosity, and mimics the properties of the extracellular matrix of the central nervous system. These factors make them an ideal scaffold for drug delivery through the blood-brain barrier and tissue regeneration (using stem cells). Thus, the use of biomaterials as suitable matrix for therapeutic purposes has emerged as a promising area of neurosciences. In this review, we describe the application of biomaterials, and the current advances, in treatment of statistically common neurological disorders.